Magnetosomes – Bacterial Magnetic Nanoparticles - Molcan, Matus; Hashim, Anezka; Kovac, Jozef; Gojzewski, Hubert; Skumiel, Andrzej; Royer, Francois; Jamon, Damien; Kopcansky, Peter; Timko, Milan (Communications - Scientific letters of the University of Zilina, 2014)
The magnetic properties, magneto-optical effects and hyperthermia effect were studied in solution of magnetosomes extracted from cultivated bacteria Magnetospirillum sp. AMB-1. The properties of magnetosomes were changed using different conditions during synthesis and by modification of particles after synthesis by using sonication and ultracentrifugation methods. It was shown that adding a higher amount of Wolfe’s vitamin solution (WVS) or ferric quinate (FQ) cause increase of the mean diameter from 47 nm (normal condition) up to 52 nm and 58 nm respectively. Hyperthermic measurements were performed for three types of magnetosome samples: (I) M - not influenced by separation method (long - chains magnetosomes), (II) UM - after centrifugation procedure, and (III) SM - after centrifugation procedure including sonication. The Specific Absorption Rate (SAR) decreased depending on chains shortening and decrease in hysteresis too. The SAR values were 1083, 934 or 463 W/g for the sample M, UM and SM, respectively.